Systematical identification of innovations in contemporary format of their classification - Лук’яненко, Ольга Дмитрівна (Technology audit and production reserves, 2015)
The paper studies the pressing issue of identification and classification of innovations which is, on the one hand determined by high dynamics in scientific and technical progress, and on the other hand by the qualitative changes in the terms of economic development of the countries and regions of the world under the influence of globalization. The evolution of modern theories of innovations has been reviewed in the context of post-globalization trends; the criteria of their classification have been determined with the isolation of the level of protection of intellectual property rights and the specification of types using traditional criteria. The classification positioning of innovations in terms of their source and method of emergence, areas of activity and efficiency has been improved. Taking into consideration the key role of the institute of the intellectual rights in national, international and global innovative systems, the elements of classification of innovations with the special attention to the question of protection of rights and copyright have been determined. Particular attention has been paid to economic innovations with the isolation of management ones (commodity, processing, service), as well as organizational (scientific and methodological, consulting, auditing, juridical) innovations among them. The conclusion about the necessity of permanent update of the classification of the innovations as a theoretical basis for the justification of the corporate and national strategies of the innovative development has been made.